Strategi Pembelajaran PAI Yang Inovatif Untuk Meningkatkan Kompetensi Dan Karakter Peserta Didik - Ahmad Muhyidin; As'adurrofiq As'adurrofiq; Iqlilul Amin (Journal of Humanities, Social Sciences, and Education, 2025)
Islamic Religious Education (PAI) learning plays a strategic role in shaping students' academic, spiritual, and character competencies. However, the dynamic development of science, technology, and student character requires innovation in learning strategies so that Islamic values ​​can be understood in a relevant and contextual manner. This article aims to examine various innovative PAI learning strategies based on a literature review of national and international journals from the past decade. The method used is a literature review, analyzing articles related to PAI learning, character education, and innovative pedagogical approaches such as blended learning, project-based learning, problem-based learning, scientific approaches, and the use of digital media. The study results indicate that innovative learning strategies in PAI not only improve students' cognitive competencies such as religious literacy, critical thinking skills, and understanding of learning materials but also strengthen affective and psychomotor aspects through the internalization of character values ​​(discipline, responsibility, tolerance, honesty, and spirituality). Learning innovations that emphasize active participation, problem-solving, collaboration, and the use of technology have proven to be more effective than traditional lecture-only methods. This study recommends strengthening the pedagogical competence of Islamic Religious Education (PAI) teachers in designing creative, contextual, and 21st-century learning without neglecting the core values ​​of Islamic teachings. Therefore, innovation in Islamic Religious Education (PAI) learning strategies is an urgent need to shape a generation with character, religiousness, and competence amidst global challenges.